ORGANIZATIONAL READINESS FOR ARTIFICIAL INTELLIGENCE WITH SYSTEMATIC MAPPING STUDY IN PUBLIC AND PRIVATE SECTORS - Muhyi, Herwan Abdul; Sukmadewi, Rani; Chan, Arianis; Kahfi, Arbi Abdul (Sosiohumaniora, 2024)
Artificial Intelligence (AI) in organization is well-established in practice and has emerged as an exciting research area in recent years. However, no comprehensive review of the literature on organizational readiness for AI has been conducted. The aim of this paper is to map the current state of research of organizational readiness for AI. We conducted a systematic mapping study and found 32 relevant primary studies. Our findings are organised into two aspects. First, systematise and classify existing research in terms of number of papers published, year of publication, type of the research, country of origin, research methods, theories, and framework used. Second, to identify research gaps and propose a research agenda in the future. Most articles published after 2019 are dominated by exploratory, empirical and descriptive research and use qualitative and quantitative methods as an approach to conducting research. However, research on organizational readiness for AI is still often carried out in developed countries. The research contributes a thematic analysis of research variables, factor AI adoption, the results of AI implementation, theory and framework, research gaps in the literature, and an agenda for future research. More academic work needs to be done on organizational readiness for AI to improve conceptual clarity, theory building and development, understanding benefits and value for the business, understanding contextual factors, and critically exploring outcomes.